Review: KRAS mutations are influential in driving hepatic metastases and predicting outcome in colorectal cancer - Steele, Colin W.; Whittle, Thomas; Smith, J. Joshua (Chinese Clinical Oncology; Vol 8, No 5 (October 09, 2019): Chinese Clinical Oncology (Molecular Markers in Colorectal Cancer), 2019)
Metastatic colorectal cancer (CRC) is a topic of intense research. KRAS mutations have emerged as aggressive drivers of disease. Here we discuss the role of KRAS mutations in metastatic progression of CRC. We describe how KRAS has become a useful biomarker in metastatic CRC and examine where future trials may look to target KRAS mutant tumors for therapeutic benefit.